Genetic characterization of the Hartón del Valle, Angus, Brangus, Holstein, and Senepol cattle breeds in Colombia, using ten microsatellite markers (2010)
ABSTRACT: The objective of this paper is to establish a genetic characterization of the Senepol (S, n=49), Holstein (H, n= 60), Hartón del Valle (HV, n=60), Angus (A, n=61) and Brangus (Br, n=60) cattle breeds in Colombia, by using the following microsatellite markers: SPS115, INRA64, ETH225, ETH10, BM1824, INRA37, TGLA122, TGLA126, INRA32, and BM2113. A total of 142 alleles were obtained for ten analyzed loci, considering the five cattle breeds as a whole. The number of alleles per locus ranged from 9 (INRA64 and 1824) to 22 (TGLA122). The expected heterozygosity was between 0.79 (INRA32) and 0.90 (INRA37) in all the cattle breeds, respectively; and medium heterozygosity was 0.84. The average number of alleles per breed varied from 9.2 in the Senepol breed to 10.3 in the Holstein breed. The expected heterozygosity range varied from 0.75 in the Hartón del Valle breed and 0.82 in the Holstein breed, with an average of 0.79. Hardy Wienberg disequilibrium was observed (p>0.05) when the populations were analyzed with all the markers. All the populations presented a heterozygote deficit, which could be the result of a strong endogamy tendency within all the herds. The markers used in this study allowed a genetic characterization of the analyzed populations. The microsatellites panel in the Hartón del Valle breed should be increased in order to increase the reliability value. Microsatellite panels could solve parenthood cases for the remainder breeds.